Long-term follow-up of HIV-infected patients on dolutegravir monotherapy. (4th December 2019) - Tebano, G; Soulié, C; Schneider, L; Blanc, C; Agher, R; Seang, S; Valantin, M A; Palich, R; Tubiana, R; Peytavin, G; Marcelin, A G; Assoumou, L; et al.
Abstract: Background: In recent years, dolutegravir monotherapy has been explored as a drug-reduced regimen for HIV patients. Methods: This was a retrospective observational study, including patients virologically suppressed for ≥6 months, without previous virological failure (VF) under integrase inhibitors (INIs), who had been switched to dolutegravir monotherapy (50 mg/day). The primary aim was to report the proportion of VF at week 48 (W48) and week 96 (W96) of dolutegravir monotherapy. The evolution from baseline to W48 of residual viraemia on ultra-deep sequencing and HIV DNA was also evaluated. Results: Sixty-one patients were included. Prior to switching to dolutegravir monotherapy, they had a median (IQR) of 15.4 (6.5–19.9) years of antiretroviral exposure, 5.8 (3.2–10.3) years of viral suppression and 687 (461–848) CD4+ cells/mm 3 . They remained on dolutegravir monotherapy for a median (IQR) of 100 (29–148) weeks. Forty-two out of 61 patients (68.9%) reached W48 and 32 out of 61 patients (52.5%) reached W96. VF occurred in three patients, with the emergence of INI resistance. VF occurred before W24 and in patients pre-exposed to INIs. At W48, the probability of VF (Kaplan–Meier analysis) was 5.6% (95% CI = 1.8%–16.4%). The same result was obtained at W96. Detectable residual viraemia did not increase and median HIV DNA did not change significantly (2.4 log/10 6 cells at baseline and 2.3 log/10 6 cells at W48). Dolutegravir plasma concentration was above the IC90 in 41/41 samples, from 22 patients. Conclusions: Long-term follow-up showed a low risk of VF under dolutegravir monotherapy, in a selected population of patients with previous long-term virological suppression and low HIV reservoir.